Social Media as a Tool for Political Mobilization: A Case Study of the 2020 Hong Kong Protests - Xinyue, Dong (Journal of Public Representative and Society Provision, 2023)
This paper aims at analyzing how social media approves activism but also weakens it at the same time. Through an analysis of social media posts, interviews with key stakeholders, and documentary evidence, the research explores four key themes: The latter include Decentralized Coordination, where Octavia Butler uses focalization to correlate Schmidt’s narrative control with the observation of the subjects; Surveillance and Censorship, where her Parables explore the capacities for global solidarity. The study shows that, although, platforms such as Telegram and Twitter played a crucial role on enabling decentralised coordination and influencing global narratives of protest, they also predisposed protestors to explicit threats that ranged from surveillance, censorship amongst others and disinformation campaigns. The paper shows how the process of political mobilisation through social media is not straightforward or slack, as it underlines the theoretical and practical issues that arise on that matter. This research fills the gap in knowledge and adds to the discussion regarding the applicability of technology, namely social media in the continuation of political activism in oppressive states.